Composições curriculares na educação infantil : por um aprendizado afetivo - Prates, Maria Riziane Costa (2012)
The text problematizes the interdiscursivities about curriculum and childhood with teachers and children in a municipal Child Educational Center in the city of Serra - Espírito Santo. It maximizes the emergence of other possible singularities in the curricular practices, from the inventive movements instituted in educational experiments: continuing education, classroom and other spaces; organization plans and immanence, in the expansions produced as an art of the encounter by playing, music and life experiences in the difference as affection assemblages, favoring an inventive learning. Its main theoretical intercessors are: Gilles Deleuze, Felix Guattari and Michel Foucault in his dialogues with Espinosa. It uses a interdiscursive, cartographic method, in the school daily life, through a micropolitical perspective of analysis, concerning curriculum movements in order to understand the curriculum practices that promote a more beautiful life in early childhood education. Thus, the process proved to be potent and happy, from the partnerships established, the work shared by the teaching staff and the visibility of otherness and minority childhoods. Therefore, writing curricula in early childhood education for affective learning requires going beyond the established. In the imbrications of the instituted and instituting curriculum, it becomes necessary the qualification and empowerment of the collective in school, valuing the children’s inventive thoughts, their pulsating and latent rhythms.